Fuzzy PI-type controller design for boost converter. Issue 1 (2nd January 2017) - Seo, Sang-Wha; Park, Jin-Soo; Kim, Yong; Choi, Han Ho
ABSTRACT: We consider the fuzzy controller design problem for a boost DC-DC converter. We design a fuzzy PI-type controller based on the common control engineering knowledge that the transient control performance can be improved if we increase the P and I gains as the error grows. Using Kharitonov's theorem, we derive a closed-loop control system stability condition which can be used to tune the fuzzy PI control parameters. Finally, we give simulation and experimental results to show the effectiveness and practicality of the proposed method.